Арктический экзамен: Повести / Н. В. Денисов - Денисов Н. В. (Современник, 1988)
Экземпляры: ф-21 (ретроконверсия) / Инвентарный номер: 23312 / Цена: 1.60 / Сис.шифр: Р2 / Авт.знак: Д33 / ГРНТИ: 17 / ББК: 84(2=411.2)6